Diagnostic accuracy of Quantitative Colour Doppler Flow imaging in distinguishing Persistent Fetal Vasculature from Retinal Detachment. Issue 2 (24th February 2021) - Chiaroni, Pierre‐Marie; Chapron, Thibaut; Purcell, Yvonne; Zuber, Kevin; Savatovsky, Julien; Caputo, Georges; Gillard, Perrine; Elmaleh, Monique; Bergès, Olivier; Lecler, Augustin
Abstract: Purpose: Distinguishing posterior persistent fetal vasculature (PFV) from retinal detachment (RD) may be very challenging clinically and ultrasonographically, as they share common morphological features. However, it is crucial, considering their substantially distinct management and treatment. We aimed to assess the relevance of quantitative colour Doppler flow imaging to distinguish PFV from RD in children. Methods: This retrospective bi‐centre study included 66 children (30 females and 36 males, mean age: 244 ± 257 days) with a clinically suspected diagnosis of RD or posterior PFV. All children underwent systematic and standardized conventional ultrasonography and colour Doppler flow imaging under general anaesthesia with a qualitative and quantitative analysis of the retrolental tissue's vascularization. Peak systolic velocity, end‐diastolic velocity and resistive index were recorded for analysis. Whenever available, surgical findings were deemed gold standard for diagnosis. A Mann–Whitney U ‐test was used to compare quantitative colour Doppler flow imaging data. Results: Peak systolic velocity and end‐diastolic velocity were significantly lower in children with PFV versus RD: 2.7 (IQR: 0.5) versus 5.1 (IQR: 2.8), p < 0.001, and 0.0 (IQR: 0.0) versus 2.0 (IQR: 1.2), p < 0.001, respectively. Resistive index was significantly higher in children with PFV versus RD: 1 (IQR: 0) versus 0.6 (IQR: 0.1), p < 0.001. Area under curves (AUCs) were of 0.94, 0.99 and 1, respectively. No differences between PFV and RD were observed on structural ultrasound or qualitative analysis of colour Doppler. Conclusion: Quantitative colour Doppler flow imaging has an excellent accuracy in distinguishing PFV from RD in children. It may help to improve management and treatment.